UMP campus community got together to perform the ‘korban’ - Siti Nur Azwin, Zulkapri (2019)
Universiti Malaysia Pahang (UMP) campus community organised the religious ritual of sacrifice or ‘korban’ of six cows in conjunction with the Hari Raya Aidiladha celebration organised by the Islamic Centre and Human Development (PIMPIN) on August 14, 2019.